Correspondence and papers of Florence O'Donoghue as secretary of the Diarmuid Lynch Memorial Fund, - O'Donoghue, Florence, 1895-1967 (1951)
Including correspondence with Kathleen Lynch, M.J. Costello, Richard Dalton and R. J. Hayes regarding the disposal of Lynch’s papers and the dispersal of funds. Includes red folders.